Coupling of mitochondrial state with active zone plasticity in early brain aging - Lu Fei; Yongtian Liang; Ulrich Kintscher; Stephan J. Sigrist (Redox Biology)
Neurodegenerative diseases typically emerge after an extended prodromal period, underscoring the critical importance of initiating interventions during the early stages of brain aging to enhance later resilience. Changes in presynaptic active zone proteins (''PreScale'') are considered a dynamic, resilience-enhancing form of plasticity in the process of early, still reversible aging of the Drosophila brain. Aging, however, triggers significant changes not only of synapses but also mitochondria. While the two organelles are spaced in close proximity, likely reflecting a direct functional coupling in regard to ATP and Ca2+ homeostasis, the exact modes of coupling in the aging process remain to understood.We here show that genetic manipulations of mitochondrial functional status, which alters brain oxidative phosphorylation, ATP levels, or the production of reactive oxygen species (ROS), can bidirectionally regulate PreScale during early Drosophila brain aging. Conversely, genetic mimicry of PreScale resulted in decreased oxidative phosphorylation and ATP production, potentially due to reduced mitochondrial calcium (Ca2+) import.Our findings indicate the existence of a positive feedback loop where mitochondrial functional state and PreScale are reciprocally coupled to optimize protection during the early stages of brain aging.